An Asian multicenter retrospective study on persistent pulmonary hypertension of the newborn: incidence, etiology, diagnosis, treatment and outcome. (17th June 2020) - Nakwan, Narongsak; Jain, Suksham; Kumar, Kishore; Hosono, Shigeharu; Hammoud, Majeda; Elsayed, Yasser Yahia; Ariff, Shabina; Hasan, Babar; Khowaja, Waqar; Poon, Woei Bing
Abstract: Objectives: To explore the incidence, etiologies, diagnostic methods, treatment options and outcomes in neonates with persistent pulmonary hypertension of the newborn (PPHN) and to identify mortality risk factors in a study from six Asian countries. Methods: A retrospective chart review of patients with documented PPHN from seven centers in six Asian countries (Japan, Kuwait, India, Pakistan, Singapore, and Thailand) between 1 January, 2014 and 31 December, 2016, was performed. Results: A total of 369 PPHN infants were identified. The incidence of PPHN ranged from 1.2 to 4.6 per 1000 live births. The all-cause mortality rate was 20.6% (76 of 369). Meconium aspiration syndrome was the primary cause of PPHN (24.1%). In most cases (84.8%) echocardiography was used to establish the diagnosis of PPHN. Sildenafil was the most commonly used pulmonary vasodilator (51.2%). Multivariate multiple regression analysis indicated gestational age <34 weeks (adjusted odds ratio (OR) = 3.27; 95% CI 1.56–6.74), congenital diaphragmatic hernia (CDH)/lung hypoplasia (LH) (adjusted OR = 6.13 (95% CI 2.28–16.42)), treatment with high frequency oscillation ventilation (HFOV) with or without inhaled nitric oxide (iNO) (adjusted OR = 3.11 (95% CI 1.52–6.34)), and inotropic agents (adjusted OR = 9.43 (95% CI 2.71–32.83)) were independently associated with increased risk of death. Conclusions: The incidence of PPHN in the current study was higher than in western settings. Birth weight, gestational age, CDH/LH, HFOV/iNO, and inotropic agents were significant mortality risk factors.